TREND OF MALARIA TRANSMISSION 2018-2022 AND ELIMINATION AGENDA IN MAPPI DISTRICT - Doni Lasut; Maria Holly Herawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
The WHO Global Malaria Programme (GMP) oversees and directs the global initiatives of the World Health Organization (WHO) aimed at controlling and eradicating malaria.. Its work is guided by the